2013
DOI: 10.1007/s15010-013-0451-x
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic anaemia after oral artemether–lumefantrine treatment in a patient affected by severe imported falciparum malaria

Abstract: Artemisinin and its derivatives are essential components of artemisinin-based combination therapies for treating severe falciparum malaria. In this paper, we describe the occurrence of haemolysis after oral artemether-lumefantrine treatment. To the best of our knowledge, this is the second reported case of a patient affected by severe falciparum malaria with haemolytic anaemia that is likely associated with oral artemether-lumefantrine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][21][22][23][24] One study was excluded from further analysis, 12 since the reported patients were part of a second publication, which was used for the purpose of this systematic review. 13 In addition to the above-mentioned scientific papers, reports by the Centers for Disease Control and Prevention (CDC, Atlanta, USA) 25 and by the Medicines for Malaria Venture (Geneva, Switzerland) were identified and included in this analysis 26 ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18][19][21][22][23][24] One study was excluded from further analysis, 12 since the reported patients were part of a second publication, which was used for the purpose of this systematic review. 13 In addition to the above-mentioned scientific papers, reports by the Centers for Disease Control and Prevention (CDC, Atlanta, USA) 25 and by the Medicines for Malaria Venture (Geneva, Switzerland) were identified and included in this analysis 26 ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19]21,23,24,26 Thirty-three cases have been published in research papers and four cases are referred to in a meeting report (one from China, one from the USA, and two from Canada). 26 In addition, surveillance data from France were discussed in that report but have not yet been published and were therefore not available for the purpose of this review.…”
Section: Description Of Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there were also reports of delayed hemolytic anemia after treatment with another artemisinin derivative, artemether, suggesting that this syndrome could occur after treatment with any of the whole class of medicines. 6 It had previously been demonstrated that malaria parasites killed by artesunate are removed from erythrocytes by the spleen. These "pitted" erythrocytes (or as referred to by Jauréguiberry et al, once-infected erythrocytes [o-iE]) remain in circulation but with a considerably decreased life span of ;7 to 21 days.…”
mentioning
confidence: 99%
“…Accumulating evidence supports an association between intravenous artesunate (and possibly other artemisinin derivatives) 22 and delayed hemolysis. All patients receiving intravenous artesunate should have systematic follow-up of hemoglobin levels up to 4 weeks post treatment.…”
Section: Resultsmentioning
confidence: 99%